MANAJEMEN KEUANGAN KEWIRAUSAHAAN DILIHAT DARI ANALISIS BREAK EVEN POINT - Diana Widhi Rachmawati; Suyanto Suyanto; Ernia Yusnita (Jurnal RATRI (Riset Akuntansi Tridinanti), 2021)
Researchers in this case use quantitative research methods, which are a research method based on philosophy and are also used for research that focuses on a particular population or sample, sampling is carried out randomly as well as using research instruments as data tools, while statistical quantitative data analysis which have been specified. The sample of this research is Warung Martabak Ibu Rosida which is located in Sungsang III, Banyuasin Regency, South Sumatra.The final result of this research is entrepreneurial financial management seen from the break-even point analysis (a case study at Mrs. Rodiah's martabak shop in the Sungsang III area, Banyuasin Regency, South Sumatra) has reached the break-even point or in other words a return on investment, it's just that the return on investment has not achieve as expected. The hope for Mrs. Rodiah's martabak shop in the Sungsang III area of Banyuasin Regency, South Sumatra) is to add to the existing product variants, while the local government needs to get attention to get loan funds from small and medium enterprises to increase production and expand the Warung Martabak business of Mrs. Rosida.Keywords: Entrepreneurial Financial Management